Saxifraga aizoides Linnaeus. - Collecte 3920. - Mont Saint-Pierre. - Marie-Victorin, Frère; Boivin, Bernard; Raymond, Marcel; Kucyniak, James (1940)
Habitat : Dans les schistes humides sur les hauteurs de l'éboulis